2011
DOI: 10.1074/jbc.m110.191510
|View full text |Cite
|
Sign up to set email alerts
|

The Chondroitin Sulfate A-binding Site of the VAR2CSA Protein Involves Multiple N-terminal Domains

Abstract: Malaria during pregnancy is a major health problem for African women. The disease is caused by Plasmodium falciparum malaria parasites, which accumulate in the placenta by adhering to chondroitin sulfate A (CSA). The interaction between infected erythrocytes and the placental receptor is mediated by a parasite expressed protein named VAR2CSA. A vaccine protecting pregnant women against placental malaria should induce antibodies inhibiting the interaction between VAR2CSA and CSA. Much effort has been put into d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
92
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 80 publications
(97 citation statements)
references
References 36 publications
(56 reference statements)
5
92
0
Order By: Relevance
“…In addition, we have recently shown that the core CSAbinding site lies within the DBL2X-CIDR PAM region. Specifically, we found two overlapping VAR2CSA fragments (DBL1X-CIDR PAM and ID1-DBL3X) showing CSA affinity comparable with that of the full-length protein (19). Srivastava et al (20) showed the same binding characteristics for DBL1X-DBL3X.…”
supporting
confidence: 51%
See 4 more Smart Citations
“…In addition, we have recently shown that the core CSAbinding site lies within the DBL2X-CIDR PAM region. Specifically, we found two overlapping VAR2CSA fragments (DBL1X-CIDR PAM and ID1-DBL3X) showing CSA affinity comparable with that of the full-length protein (19). Srivastava et al (20) showed the same binding characteristics for DBL1X-DBL3X.…”
supporting
confidence: 51%
“…Solid Phase Binding Assay (ELISA)-The solid phase binding assay was performed as previously described (19). Briefly, microtiter plates were incubated with chondroitin sulfate proteoglycan (CSPG) (bovine decorin, D8428, Sigma) and heparan sulfate proteoglycan (HSPG) (H4777, Sigma) overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations